The Demes of Attica, 508/7 -ca. 250 B.C. : A Political and Social Study - Whitehead, David, 1949- (Book collections on Project MUSE., 1986)
This work is a richly detailed study of the nature and development of the 139 Attic demes, the local units that made up the city-state of Athens during the classical and early Hellenistic periods. Originally published in 1986. The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These paperback editions preserve the original texts of these important books while presenting them in durable paperback editions. The goal of the Princeton Legacy Library is to vastly increase access to the rich scholarly heritage found in the thousands of books published by Princeton University Press since its founding in 1905.